Examining media’s coverage of COVID-19 vaccines and social media sentiments on vaccine manufacturers’ stock prices - Bai, Shun Yao; Lee, Edmund W. J. (Frontiers in Public Health, 2024)
The COVID-19 pandemic caused a widespread public health and financial crisis. The rapid vaccine development generated extensive discussions in both mainstream and social media, and sparked optimism in the global financial markets. This study aims to (a) explore the key themes from mainstream media's coverage of COVID-19 vaccines on Facebook, and (b) examines how public interactions and responses on Facebook to mainstream media's posts are associated to daily stock prices and trade volume of major vaccine manufacturers. We obtained mainstream media's coverage of COVID-19 vaccines and major vaccine manufacturers on Facebook, as well as the corresponding trade volume and daily closing prices from January 2020 to December 2021. Structural topic modelling on social media posts revealed ten distinct topics evolving over the pandemic, covering areas such as vaccine trials, politicization, and stock market discussions. Regression analysis showed that Facebook reactions had inconsistent effects on stock prices, with specific reactions 'Haha' and 'Angry' having the most discernible impact on stock prices of major vaccine manufacturers. However, social media reactions had very little observable impact on trade volume. Theoretical and practical insights into the complex interplay between public sentiment and financial markets were discussed.